Significance of Radiological Findings in Patients with Respiratory and Abdominal Manifestations of Covid-19 - Ashraf, Talaat Youssef (Journal of Etiological Diagnosis, 2021)
The autopsy findings of patients died from Covid -19 showed that pulmonary and multiorgan small vessels thromboembolism is an essential features of the disease. Small vessels thromboembolism is frequently not detected by means of laboratory and radiological investigations. The current perspective reviewed the different radiological findings in patients with covid -19 suffering from respiratory and/or abdominal symptoms and also reviewed the recent studies which used the contrast enhanced ultrasound in the diagnosis of patients with pulmonary and multiorgan small vessels thrombosis.
Keywords: Covid-19. pulmonary thromboembolism; Contrast enhanced ultrasound; Covid -19 vasculopathy; Management of Covid-19.